Stres Kerja pada Perawat di Lembaga Pemasyarakatan - Esra Devi Tarida Lubis; Siti Saidah Nasution; Riswani Tanjung (Journal of Telenursing (JOTING), 2022)
This study aims to identify the work stress of nurses in Correctional Institutions (LP). The method used is a systematic review by searching articles on the Proquest, Pubmed and ScienceDirect databases with the keywords "occupational stress" AND "correctional facilities". The study results show that nurses' work stress in correctional institutions is closely related to work environment factors, prison inmate population and correctional management. In conclusion, work stress and fatigue among nurses in correctional institutions occur due to work environment factors, including high workload, the characteristics of prisoners and convicts, and the system that regulates correctional institutions, which can decrease work productivity and quality of care. Keywords: Correctional Institutions, Nurses, Work Stress